2010
DOI: 10.1177/112067211002000423
|View full text |Cite
|
Sign up to set email alerts
|

Fundus Autofluorescence and Spectral Domain Optical Coherence Tomography in Early Detection of Plaquenil Maculopathy

Abstract: Findings on SD-OCT and FAF imaging support the histopathologic findings described in cases of hydroxychloroquine maculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
1
4
0
2
Order By: Relevance
“…Rodriguez-Padilla et al16 first described some of the findings in HCQ toxicity on a research prototype ultra-high resolution OCT machine, and other recent case reports have reported HCQ retinopathy findings on SD OCT machines 25,26. In our study, SD OCT abnormalities due to HCQ toxicity were identified in five patients when using both SD OCT systems.…”
Section: Discussionsupporting
confidence: 57%
“…Rodriguez-Padilla et al16 first described some of the findings in HCQ toxicity on a research prototype ultra-high resolution OCT machine, and other recent case reports have reported HCQ retinopathy findings on SD OCT machines 25,26. In our study, SD OCT abnormalities due to HCQ toxicity were identified in five patients when using both SD OCT systems.…”
Section: Discussionsupporting
confidence: 57%
“…[23] Also, previous case reports demonstrated retinal thinning mainly in the inferior quadrant of the parafoveal and perifoveal area. [2425] Further studies are warranted to confirm these results.…”
Section: Discussionmentioning
confidence: 84%
“…Hassentein and Meyer, in a recent review, reported a high correlation between histological structure of the retina and the image acquired by spectral domain (SD)-OCT [5]. Other studies have demonstrated the usefulness of SD-OCT in visualization of microscopic structures of the retina, like disruption of the photoreceptors inner/outer segment junctions (IS/OS) in cases of chloroquine toxicity [6], serpiginous choroiditis [7], and acute multiple evanescent white dot syndrome [8], and disruption that was followed by recovery of the IS/OS in some cases of acute zonal occult outer retinopathy (AZOOR) [9]. …”
Section: Introductionmentioning
confidence: 99%